Electrical nerve stimulation for sensory-neural pathway reconstruction in upper-limb amputees - Wang, Yingying; Liu, Hongyu; Zeng, Peiying; Ji, Lingchao; Zhou, Yaqi; Zhou, Liufang; Tao, Yuan (Frontiers in Neuroscience, 2023)
Due to the destruction of neural pathways between the stump limbs and the brain, the absence of natural sensory function seriously affects the rehabilitation of limb function and the daily life of amputees. Physical stressors from external environments such as mechanical pressure and transcutaneous electrical nerve stimulation (TENS) could be potential non-invasive technologies for recovering the somatic sensation of amputees. Previous studies insight that stimulating residual or regenerated nerves in stumps of some amputees could make them feel intuitive sensations of their phantom hands, but it is still imperfect due to unstable physiological responses caused by inaccurate stimulus parameters and positions. In this paper, an optimal TENS strategy was developed by exploring the distribution of nerves in the stump skin associated with evoking phantom sensations, known as phantom hand map. Additionally, the effectiveness and stabilities of the confirmed stimulus configuration were evaluated via designing single-stimulus and multi-stimuli paradigms in a long-term experiment. Besides, the evoked sensations were then evaluated via recording electroencephalogram (EEG) and exploring brain activities during a long-term experiment. Results demonstrated that various kinds of intuitive sensations for amputees were stably induced by adjusting frequencies of TENS. Especially under frequencies of 5 and 50 Hz, a 100% stability of sensory types was achieved when the stimuli were acted on in two of the selected stimulus locations. Furthermore, at these stimulus locations, the stability of sensory positions was up to 100% across different days. Moreover, the evoked sensations were objectively supported by the brain responses represented by specific patterns of event-related potentials. This work could provide an effective method for developing and evaluating a physical stressor stimulus strategy, which could make an important role in the somatosensory rehabilitation for amputees and even more patients suffering in somatomotor sensory dysfunction. More importantly, the paradigm developed in this study can provide effective guidelines for stimulus parameters in physical electrical nerve stimulation treatments of a variety of symptoms related to neurological disorders.